36. ASSESSMENT OF PATIENT FAMILY MEMBERS' KNOWLEDGE OF RISK FACTORS AND WARNING SIGNS OF STROKE AT PHU THO GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objectives: Assessment of Family Members' Knowledge of Risk Factors and Warning Signs of Stroke at the Stroke Center, Phu Tho General Hospital (2024).Methods: Cross-sectional descriptive  study.Results: The study conducted on 196 family members of patients at the Stroke Center, Phu Tho General Hospital, revealed that their knowledge of the risk factors for stroke varied. Hypertension (92.3%) was the most commonly recognized risk factor. Other risk factors, such as smoking (62.7%) and lack of physical activity (63.8%), were less well-known. Weakness, paralysis of one side of the body, and dysphasia were the most recognized warning signs of stroke, with 94.9% and 91.3% awareness rates, respectively. Analysis of the correlation between knowledge of stroke risk factors showed that individuals aged ≤ 50 had a 5.53 times higher level of knowledge than those > 50 years old. Those with a profession had a 3.16 times higher level of knowledge than the unemployed, and residents of Viet Tri City had a 1.84 times higher level of knowledge compared to those living elsewhere, differences were statistically significant with p 50 years old, and residents of Viet Tri City had 2.44 times better knowledge compared to those living elsewhere (p
Keywords: Knowledge; risk factors; warning signs; stroke